Copyright Law Protection Competence in Paying Royalty as Exclusive Rights Substance - ISRAHADI, Evita Isretno (Journal of Advanced Research in Law and Economics, 2020)
Copyright is considered as a moving and intangible object; therefore, a copyright devolution cannot be done verbally but must be with an authentic deed or Underhand deed. Problem Identification: 1. How does the song copyright devolution mechanism make economic interest for a composer or Copyright Holder? 2. What is the system of song copyright royalty payment in Indonesia? and 3. What should be done by the parties to resolve the royalty payment execution dispute? It is a normative juridical method that must be used. Research Result: It is true that copyright license mechanism, fee retaining or royalty payment is considered as logic consequences that must be done by a licensee over a licenser (Copyright holder). It is because the licensee gets material profits due to the economic rights exploitation over the copyright itself.  There are many varieties or different ways of compensation payment system or indemnification from the licensee to the licenser over one copyright object to another, for instance in song/music is known two different ways such as royalty and flat systems, while in music or song is known several ways, namely by percentage system, period system, profit sharing system,  compensation or  copyright selling system. Royalty payment dispute resolving may come in many ways, and, generally, the dispute resolving forums are available into two forms, such as litigation forum through courts and non-litigation forum out of court.